Alternative therapy of menopausal vegetative disorders in women taking the metabolic status into account - О.А. Taran; D.H. Konkov; O.V. Bulavenko; T.V. Lobastova; O.B. Malinina; N.M. Homon; I.R. Pyvniuk (Репродуктивная эндокринология, 2023)
Research objectives: to study the clinical effectiveness of alternative complex therapy of vegetative syndrome in menopausal patients using L-arginine and xylitol drugs. Materials and methods. The clinical prospective study included 50 patients in the early postmenopausal period with natural menopause, neurovegetative and psychoemotional manifestations of the climacteric syndrome. According to the Life extension strategy, patients received intravenous L-arginine (Tivortin drug) and xylitol solution with electrolytes (Xylat drug) for endothelial protection and correction of insulin resistance in order to treat climacteric syndrome. Modified Kupperman menopausal index, serum triglyceride, cholesterol, high-density lipoprotein, low-density lipoprotein, and very-low-density lipoprotein levels were determined in all women. Examinations were performed before the start of therapy and 3 months after the end of treatment. Results. The Life extension therapeutic strategy as an alternative comprehensive therapy of the vegetative syndrome in menopausal patients contributed to a reliable reduction of the manifestations of the climacteric syndrome. The advantage of combined therapy involving L-arginine and xylitol was manifested in a significant decrease in diastolic blood pressure (p = 0.043); reduction of the Kupperman index (p = 0.002) and the average score of vasomotor symptoms (p = 0.02). There was also a significant decrease in the serum level of insulin (p = 0.00007), HOMA index (p = 0.01), low-density lipoproteins (p = 0.04), and triglycerides (p = 0.03). The selected therapy was well tolerated during the observation period. Conclusions. The combined therapy involving L-arginine and xylitol in the early postmenopausal period with neurovegetative and psychoemotional manifestations of the climacteric syndrome had a pronounced clinical effect, which consisted in a significant reduction of vegetative disorders and stabilization of carbohydrate and lipid metabolism. The given therapeutic strategy can be considered as an alternative therapy in patients with climacteric disorders when phytotherapy is ineffective and when there are contraindications or limitations to menopausal hormone therapy. The results of this study showed the safety of the Life extension strategy.